2015
DOI: 10.1007/s10903-015-0330-x
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and Its Associated Factors in a Sample of Colombian Immigrant Population in Spain

Abstract: Immigrants are vulnerable to Intimate partner violence (IPV). This study aims at characterising IPV among Colombian immigrants, and to identify its associated factors. Cross-sectional study on 336 Colombian immigrants (46 % women), aged 15-70 years, living in Spain. Self-reported questionnaire information on IPV suffered throughout the last year was collected face-to-face. Multivariable logistic regression was used to identify factors associated with IPV. Almost 30 % of participants reported IPV, without diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Wirtz’s qualitative work with internally displaced Colombian women found that women attributed IPV to their partner’s exposure to political violence, their partners’ lost employment, and economic insecurity as a cause of IPV (Wirtz et al, 2014). Our results are also consistent with other studies examining discrimination and IPV (Colorado-Yohar et al, 2012; Colorado-Yohar et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Wirtz’s qualitative work with internally displaced Colombian women found that women attributed IPV to their partner’s exposure to political violence, their partners’ lost employment, and economic insecurity as a cause of IPV (Wirtz et al, 2014). Our results are also consistent with other studies examining discrimination and IPV (Colorado-Yohar et al, 2012; Colorado-Yohar et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…Studies have found a high prevalence of intimate partner violence (IPV), or emotional, physical and sexual abuse by a current or former partner (Ellsberg & Heise, 2005), among women living in communities impacted by conflict and migration, but why this occurs is not well understood (Colorado-Yohar et al, 2012; Colorado-Yohar et al, 2016; Wirtz et al, 2014). Social disorganization theory provides a strong theoretical framework to explore how community-level social factors influence IPV in conflict-affected areas.…”
Section: Introductionmentioning
confidence: 99%
“…We found that all minority women were at disproportionate risk of IPV and related worry compared to majority women. Prior research suggests that minority women's disproportionate previous experiences of IPV, childhood abuse, past trauma, and witnessing parental violence; difficulty integrating into the labor market; economic constraints; disagreements with their partners about gender roles; partners' substance use, feelings of disempowerment, and dominance in decision-making; and lack of social support represent psychosocial factors which may contribute to minority women's elevated risk of IPV experiences and IPV-related worry compared to majority women (Ahonen et al, 2010;Al-Tawil, 2012;Colorado-Yohar et al, 2016;Denham et al, 2007;Lewis et al, 2017;Widom, 2017). In addition, compared to heterosexual women and women not living in poverty, sexual minority women and women living in poverty were less likely to report police noninvolvement (i.e., were more likely to report police involvement) following IPV experiences, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A may be associated with greater violence perpetration than cannabis used alone or in conjunction with problematic alcohol use. 45 Data also show that alcohol consumption/ dependence [46][47][48] and alcohol use during episodes of iPV is common. 44 according to stuart et al, women were more likely to perpetrate physical violence on drinking days relative to non-drinking days.…”
Section: Emotional and Psychological Traitsmentioning
confidence: 99%